Analisis Kebutuhan Air Irigasi Dusun Pataan Kecamatan Sambeng - Sari, Dwi Kartika; Ihsan, Jauhar (Jurnal teknika, 2022)
The purpose of this research is to analyze the irrigation area of Pataan Hamlet, Pataan Village, and find out the water balance between demand and water availability from source flow. This research uses the descriptive analysis method for agricultural water demand and comparative analysis for agricultural water balance. Water needs for rice fields can be calculated using empirical formulas, namely Consumptive Water Needs (CWR), Rice Field Water Needs (FWR), and Water Needs for All Agricultural Lands (PWR). By using the parameters of cropping factors, evaporation, percolation, effective rainfall, and irrigation efficiency. The results showed that the average water demand for the Pataan Irrigation Area Agriculture ranged from 6.30 to 19.22 liters/second, except August I to October II when the water demand was low due to the dry season which resulted in drought in most agricultural lands. The water balance shows a water deficit in November II, January II, May I, May II, June I. The highest water deficit was in May II at 3.45 liters/second, because most of the agricultural land experienced drought and harvests.